Exploring Clause Complexity: A Comprehensive Analysis of a Student’s Narrative Text on Central Kalimantan Folklore - Erisyerico, Mimo Lalito; Luardini, Maria Arina (General English Education, 2025)
Writing cohesive and engaging narrative texts requires effective use of clause complexity to convey meaning and maintain reader interest. This research examines clause complexity in a narrative text written by a student in the English Education Program at the University of Palangka Raya, focusing on Central Kalimantan folklore. Using a qualitative approach with content analysis and Systemic Functional Linguistics (SFL), the research applies Halliday and Matthiessen’s (2013) framework, emphasizing taxis (parataxis and hypotaxis) and logico-semantic relations, including expansion (elaboration, extension, and enhancement) and projection (locution and idea). The text was chosen for its thematic relevance, generic structure, language features, and clause diversity. Results show paratactic constructions dominate, comprising 77% of the total clauses, reflecting the student’s preference for coordination to ensure readability and clarity. Paratactic extension (27%) and enhancement (17%) highlight effective idea connection and context, while paratactic locution (33%) underscores the role of dialogue in engaging readers. Hypotactic constructions, at 13%, focus on idea projection and enhancement (10%), indicating limited use of subordination for expressing complex relationships. These findings underline the importance of mastering both coordination and subordination techniques for cohesive, meaningful narratives. The research provides insights for educators to enhance students' clause usage in academic writing.